Beware Zombies and Unicorns: Toward Critical Patient and Public Involvement in Health Research in a Neoliberal Context - Madden, Mary; Speed, Ewen (Frontiers in Sociology, 2017)
Patient and Public Involvement (PPI) in UK National Health Service (NHS) research has become an imperative in policy and practice. However, lack of clarity on what PPI is (or might be) has given rise to a poorly monitored, complex field of activity, variously framed by the expectations of policy makers, funders, host organisations, researchers, health professionals, individual recruits, volunteers, activists and third sector organisations. The normative shift towards PPI has taken place within a neoliberal policy context, the implications of which needs to be explicitly considered, particularly after the Brexit referendum which has left policy makers and researchers wondering how to better appeal to a distrustful public subjected to ‘post-truth’ and ‘dog whistle’ politics. This commentary examines the prospects for a more critical approach to PPI which addresses context, is evidence-informed and mindful of persistent inequalities in health outcomes, at a time when models of PPI in NHS health research tend to be conceptually vague, derived from limited clinical and managerial settings, and centred on a construction of the abstract, rational, compliant and self-managing patient or lay-person.